Optic Neuritis and Retinal Ganglion Cell Loss in a Chronic Murine Model of Multiple Sclerosis - Quinn, Thomas; Dutt, Mahasweta; Shindler, Kenneth S. (Frontiers in Neurology, 2011)
Multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE) are neurodegenerative diseases with characteristic inflammatory demyelination in the central nervous system, including the optic nerve. Neuronal and axonal damage is considered to be the main cause of long-term disability in patients with MS. Neuronal loss, including retinal ganglion cell (RGC) apoptosis in eyes with optic neuritis, also occurs in EAE. However, there is significant variability in the clinical course and level of neuronal damage in MS and EAE. The current studies examine the mechanisms and kinetics of RGC loss in C57BL/6 mice immunized with myelin oligodendrocyte glycoprotein to induce a chronic EAE disease. Clinical progression of EAE was scored daily and vision was assessed by optokinetic responses. At various time points, RGCs were counted and optic nerves were examined for inflammatory cell infiltration. Almost all EAE mice develop optic neuritis by day 15 post-immunization; however, RGC loss is delayed in these mice. No RGC loss is detected 25 days post-immunization, whereas RGC numbers in EAE mice significantly and progressively decrease compared to controls from 35-50 days post-immunization. The delayed time course of RGC loss is in stark contrast to that reported in relapsing EAE, as well as in rats with chronic EAE. Results suggest that different clinical disease courses of optic nerve inflammation may trigger distinct mechanisms of neuronal damage, or RGCs in different rodent strains may have variable resistance to neuronal degeneration.